2007
DOI: 10.1007/s00167-007-0469-7
|View full text |Cite
|
Sign up to set email alerts
|

Performance-based functional outcome for children 12 years or younger following anterior cruciate ligament injury: a two to nine-year follow-up study

Abstract: There is limited scientific knowledge on ACL injuries in children 12 years or younger. Substantial controversy exists on treatment algorithms and there are no published data on performance-based functional outcome. Classification of adult ACL injured subjects as copers and non-copers is common, but no study has classified knee function in children using performance-based functional test after ACL injury. The aim of the present study was to evaluate the medium-term functional outcome among children with ACL inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0
10

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 61 publications
6
43
0
10
Order By: Relevance
“…Compared to a control group who received acute reconstructions, they reported no increase in intra-articular injuries despite a mean delay of 70 weeks until ACL reconstruction. Moksnes et al [29] delayed ACL reconstruction in young patients until skeletal maturity with extensive rehabilitation and return to activities as tolerated with brace wear. They reported 65% of children were able to return to previous activities without reconstruction and only 9.5% suffered a secondary meniscus injury.…”
Section: Non-operative Treatmentmentioning
confidence: 99%
“…Compared to a control group who received acute reconstructions, they reported no increase in intra-articular injuries despite a mean delay of 70 weeks until ACL reconstruction. Moksnes et al [29] delayed ACL reconstruction in young patients until skeletal maturity with extensive rehabilitation and return to activities as tolerated with brace wear. They reported 65% of children were able to return to previous activities without reconstruction and only 9.5% suffered a secondary meniscus injury.…”
Section: Non-operative Treatmentmentioning
confidence: 99%
“…Woods and O'Connor 107 reported that the incidence of meniscus injuries at the time of surgery (46%) in the 13 included children was similar to the incidence in 116 skeletally mature adolescents treated with transphyseal reconstruction. Moksnes et al 82 reported 3 medial (11%) and 3 lateral (11%) meniscus injuries in 26 children during a follow-up period of 2 to 9 years, while Mizuta et al 80 reported 1 additional meniscus injury in a study of 18 skeletally immature patients (6%). Graf et al 40 reported 7 new meniscus injuries (88%) in 8 children who underwent delayed ACL reconstruction due to knee instability.…”
Section: Physeal Sparing Reconstructionmentioning
confidence: 99%
“…To our knowledge, no well-designed studies on nonoperative management have been published, and the rates of secondary meniscus injuries in 3 of 4 case series were low. 80,82,107 There is an immense need for well-designed prospective studies with well-described inclusion criteria and long-term follow-up to develop evidence-based criteria for the treatment of skeletally immature individuals.…”
Section: Treatment Decision Criteriamentioning
confidence: 99%
See 2 more Smart Citations